Renal pseudotumours caused by xanthogranulomatous pyelonephritis. Issue 8 (August 1982) - Watson, A R; Marsden, H B; Lendon, M; Jones, P H Morris
Abstract : Five cases of xanthogranulomatous pyelonephritis are described. Wilms's tumour was suspected preoperatively in 2 of the cases and a renal tumour appeared to be confirmed at laparotomy in three. Pathological examination is diagnostic and the condition appears to be always unilateral. Nephrectomy is curative.